2021
DOI: 10.1123/pes.2020-0076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 Weeks of Incremental Aerobic Training on Inflammatory Mediators, Cardiorespiratory Indices, and Functional Capacity in Obese Children With Bronchial Asthma

Abstract: Purpose: To appraise the effects of incremental aerobic training (IAT) on systemic inflammatory mediators, cardiorespiratory indices, and functional capacity in obese children with bronchial asthma. Methods: This study included 30 children with asthma (age = 8–16 y) allocated randomly into either the control group (n = 15; received the traditional pulmonary rehabilitation program) or IAT group (n = 15; engaged in 8 weeks of IAT in addition to the traditional pulmonary rehabilitation program). The systemic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A total of 12 studies (62%) 10,[27][28][29][30][31][32][33][34][35][36][37] showed that AT induced some change in the immune system inflammatory response, while 9 studies (38%) [38][39][40][41][42][43][44][45] did not show any change in the immune system. In complement, other general benefits were observed such as improvements in the aerobic fitness (10 studies), health-related quality of life (7 studies), clinical control (2 studies), reduction of symptoms of asthma (6 studies), and decrease of airways hyperresponsiveness (2 studies) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies (62%) 10,[27][28][29][30][31][32][33][34][35][36][37] showed that AT induced some change in the immune system inflammatory response, while 9 studies (38%) [38][39][40][41][42][43][44][45] did not show any change in the immune system. In complement, other general benefits were observed such as improvements in the aerobic fitness (10 studies), health-related quality of life (7 studies), clinical control (2 studies), reduction of symptoms of asthma (6 studies), and decrease of airways hyperresponsiveness (2 studies) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AT induces a modulation of the immune system 10,[27][28][29][30][31][32][33][34][35][36][37] . In this sense, the present study speculates on two categories of asthmatics, i) those who practice regular exercise or are trained; ii) and those who are untrained or sedentary.…”
Section: Possible Protective Pathways Against Covid-19 Presented By S...mentioning
confidence: 99%
“…Table 1 shows the characteristics of the 27 included studies, which included a sample of 1268 randomized subjects (695 were randomized to the exercise group); the mean age was 12.6 years (range 5.1-17.0 years). The authors classified the subjects as obese according to different classifications, such as BMI above the 95th percentile [21][22][23][24][25][26][27] ; BMI above the 97th percentile for age and sex alone [28][29][30][31] or in combination with body fat percentage >25% 28,32 or >34% 33 ; body fat percentage > 30% 34,35 ; BMI adjusted for age and gender 36 ; BMI ≥ 24 37,38 ; BMI ≥ 25 38,39 ; BMI ≥ 30 [40][41][42] ; BMI two standard deviations above the growth reference alone, 43 or in combination with waist circumference >80 cm 44 ; or presence of obesity according to the International Obesity Task Force cut-offs. 45 Nine studies included males only, [24][25][26][27]32,34,38,39,43 seven studies included females only, 23,31,33,35,42,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…45 Nine studies included males only, [24][25][26][27]32,34,38,39,43 seven studies included females only, 23,31,33,35,42,44,46 and 11 studies included a mixed sample of males and females. 21,22,[28][29][30]36,37,40,41,45,47 The average study duration was 12 weeks (range 6-26), the frequency was three times per week (range 1-5), and the workout duration was 37 min (range 4-70).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In individuals with COPD, HRR improves following exercise training programs or through oxygen supplementation in those with chronic hypoxemia ( Scalvini et al, 1999 ; Gimeno-Santos et al, 2014 ). Obese children with bronchial asthma undergoing pulmonary rehabilitation showed a significant improvement in cardiorespiratory function and HRR, as well as in the inflammatory profile and functional capacity ( Elnaggar et al, 2021 ). However, to the best of our knowledge, no study has evaluated the effects of exercise training on HRR in adult individuals with asthma.…”
Section: Introductionmentioning
confidence: 99%